Oral microbiota in oral cancer patients and healthy individuals: A scoping review - Irna Sufiawati; Alamsyah Piliang; Vatchala Rani Ramamoorthy (Dental Journal, 2022)
Background: Oral microbiota has been suggested to have a role in the etiopathogenesis of oral cancer; however, the oral microbiota diversity in patients with oral cancer compared to healthy individuals remains unclear. Purpose: This scoping review aimed to provide an overview of the current evidence regarding the oral microbiota composition colonized in oral cancer patients and its comparison with healthy individuals. Reviews: This study was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Eligible studies were searched in PubMed, Scopus, Web of Science, and ScienceDirect databases from January 2015 to March 2022. A total of 20 relevant studies were included according to the inclusion and exclusion criteria, including 14 cross-sectional studies and 6 cohort studies. All studies have identified various oral bacteria, but only one study has detected viruses and parasites diversity. A variety of oral microbiota found were 6 phyla of bacteria, 6 phyla of viruses, 7 phyla of fungi, and 7 phyla of parasitic. Seventeen studies proved that oral microbiota compositions were statistically significant differences compared to healthy controls, but not in 3 studies. Conclusion: The majority of studies showed various oral bacteria in oral cancer patients which were statistically significant difference compared to healthy controls. This study indicates the need for more research to evaluate viruses and parasites composition and diversity in oral cancer patients. Moreover, future research should focus to clarify whether the changes of oral microbial composition as a community may play a critical role in the etiopathogenesis of oral cancer.